(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article presents experimental studies of a previously developed command recognition system. The details of the proposed mobile robot are described in detail. The setup of two experiments is presented, as well as an analysis of the results obtained. The conclusions provide recommendations for improving the accuracy of command recognition.